Scandcleft randomised trials of primary surgery for unilateral cleft lip and palate: 1. Planning and management. Issue 1 (2nd January 2017) - Semb, Gunvor; Enemark, Hans; Friede, Hans; Paulin, Gunnar; Lilja, Jan; Rautio, Jorma; Andersen, Mikael; Åbyholm, Frank; Lohmander, Anette; Shaw, William; Mølsted, Kirsten; Heliövaara, Arja; et al.
Abstract: Background and aims: Longstanding uncertainty surrounds the selection of surgical protocols for the closure of unilateral cleft lip and palate, and randomised trials have only rarely been performed. This paper is an introduction to three randomised trials of primary surgery for children born with complete unilateral cleft lip and palate (UCLP). It presents the protocol developed for the trials in CONSORT format, and describes the management structure that was developed to achieve the long-term engagement and commitment required to complete the project. Method: Ten established national or regional cleft centres participated. Lip and soft palate closure at 3–4 months, and hard palate closure at 12 months served as a common method in each trial. Trial 1 compared this with hard palate closure at 36 months. Trial 2 compared it with lip closure at 3–4 months and hard and soft palate closure at 12 months. Trial 3 compared it with lip and hard palate closure at 3–4 months and soft palate closure at 12 months. The primary outcomes were speech and dentofacial development, with a series of perioperative and longer-term secondary outcomes. Results: Recruitment of 448 infants took place over a 9-year period, with 99.8% subsequent retention at 5 years. Conclusion: The series of reports that follow this introductory paper include comparisons at age 5 of surgical outcomes, speech outcomes, measures of dentofacial development and appearance, and parental satisfaction. The outcomes recorded and the numbers analysed for each outcome and time point are described in the series. Trial registration: ISRCTN29932826.